Ecoliterasi Santri: Transformasi Kesadaran Lingkungan di Pesantren Hijau Indonesia - Muhyidin, Muhyidin; Bella, Sinta; Helmi, Achmad Mahrus; Mufidah, Maria (INCARE, International Journal of Educational Resources, 2025)
This study examines ecoliteracy among students as a form of environmental  awareness transformation in green Islamic boarding schools (pesantren) in Indonesia from a literacy perspective. Pesantren are not only Islamic educational institutions but also have great potential in shaping the character of students who care about the environment. Through the integration of Islamic values, environmentally friendly practices, and an ecological literacy approach, green Islamic boarding schools create a learning ecosystem that fosters ecological awareness. This study highlights how students experience changes in their perspectives, behaviors, and active participation in environmental protection through literacy based on Islamic values and the pesantren's local context. This transformation demonstrates that ecoliteracy is not only about ecological knowledge, but also the internalization of spiritual, social, and cultural values in building sustainable environmental awareness.